An Analysis of Figurative Language in Sabrina Carpenter’s Song Album “Short N’ Sweet” - Gea, Mira Kristiyanti; Pasaribu, Tiara Kristina; Sinambela, Erika (Universitas Galuh, 2025)
The study is very important because when listening to songs, most people only focus on the music rather than the lyrics without knowing the meaning of the song. This study aims to find out the types of figurative language in “Short n Sweet” song album by Sabrina Carpenter and how is the figurative language realized in the song album. This research used mix-method research namely quantitative and qualitative. This study used Perrine (1992) theory which classified figurative language into 12 types. However, this research only focuses into 6 types of figurative language with the research results of 97 data. There are Metaphor (16), Simile (14), Personification (9), Symbol (19), Hyperbole (23), and Irony (16). The realization is that there are six types of figurative language, namely metaphors (comparing two different ideas, namely intelligence with sharpest tools and describing a partner with bee). Simile (make a direct comparison using the term